Criminal Justice Students' Perceptions of Human Trafficking Victims: Assessing Bias and Helping Behavior. Issue 1 (2nd January 2022) - Salami, Temilola; Babu, Jeeva; Hari, Cayla
Abstract: The current study used a vignette study design to determine if criminal justice students hold biases about human trafficking victims based on demographic variables (i.e. age, gender, immigrant status) and forms of trafficking (i.e. sex and labor trafficking). For this study, 190 criminal justice students were recruited. Due to stereotypes and biased views of who victims are (formed largely by biased media coverage), we hypothesized that criminal justice students would show higher mean scores on their ability to correctly identify, and lower mean scores on their willingness to help male, domestic, adult, and labor trafficked individuals as compared to female, foreign, young, and sex trafficked individuals. The results show that criminal justice students had lower mean scores on accuracy in identifying male and labor trafficked victims than female and sex trafficked victims, and lower mean scores in their willingness to help labor trafficked victims relative to sex trafficked victims. Implications and future directions are discussed.